What role does symbolism still play on German graveyards? A case study from Saxony, Germany - Lautenschläger, Thea; Lossau, Victor (Ethnobotany Research and Applications, 2024)
Background: In terms of the history of sepulchral culture in Germany, the customisation of gravesites with plants is a relatively recent but widespread practice in German-speaking countries. The diverse, temporally changing and regionally varying connections between plant and grave, and in particular the current relationship in relation to the original symbolism of plants in the Christian sense, have not been researched in detail and are the aim of this study. Methods: Between November and January 2022/2023, 458 graves were randomly selected at eleven cemeteries of the German city Dresden and their planting was photographed and determined. Plants from wreaths and flower arrangements as well as plant representations on grave markers were included in the survey. In addition, 29 relatives were interviewed about their intentions for the planting and 9 experts of garden centers were asked about trends they had observed. Results: A total of 152 plant species were identified. On average, the graves were planted with 3.8 species. Calluna, Hedera and Abies were used particularly frequently. Plant representations were found on approx. 1/3 of the grave markers, of which roses were the most common. Conclusions: The study shows a change in grave planting. Traditional Christian or more generally symbolic plants associated with death are in decline compared to longer-lasting, easier to care for, but also more colourful plants. The cemetery and the grave are becoming aesthetic places of active remembrance and togetherness with the deceased. Keywords: graveyard, cemeteries, Saxony, Germany, decoration, plants, symbols, Christianity